Intercropping legumes and intermediate wheatgrass increases forage yield, nutritive value, and profitability without reducing grain yields - Pinto, Priscila; Cartoni-Casamitjana, Stefania; Cureton, Colin; Stevens, Andrew W.; Stoltenberg, David E.; Zimbric, Joseph; Picasso, Valentin D. (Frontiers in Sustainable Food Systems, 2022)
Kernza intermediate wheatgrass (IWG) is a perennial grain and forage crop. Intercropping IWG with legumes may increase the forage yields and nutritive value but may compromise Kernza grain yields. The interaction between IWG and legumes depends on planting season, row spacing, and legume species. Our aim was to evaluate the effects of those management practices on Kernza grain yield, summer and fall forage yield and nutritive value, weed biomass and, the profitability of the cropping system in Wisconsin, USA. In the spring and fall of 2017, we planted eight cropping systems at 38 and 57 cm of row spacing: four IWG monocultures [control without N fertilization or weed removal (IWG), hand weed removal (hand weeded), IWG fertilized with urea at rates of 45 or 90 kg ha-1], and four IWG-legume intercrops (IWG with alfalfa, Berseem clover, Kura clover, or red clover). Most of the intercropping systems were similar to IWG monoculture in grain (ranging from 652 to 1,160 kg ha-1) and forage yield (ranging from 2,740 to 5,190 kg ha-1) and improved the forage quality. However, for spring planted IWG, intercropped with red clover or alfalfa, the grain and forage yields were lower than the IWG monoculture ( 80 and 450 kg ha-1, respectively). The best performing intercrops in the first year were Kura clover in the spring planting (652 kg Kernza grain ha-1, 4,920 kg IWG forage ha-1 and 825 kg legume forage ha-1) and red clover in the fall planting (857 kg Kernza grain ha-1, 3,800 kg IWG forage ha-1, and 450 kg legume forage ha-1). In the second year, grain yield decreased 84% on average. Overall, the profitability of the IWG legume intercropping was high, encouraging the adoption of dual-purpose perennial crops.